Workload disparities and their role in the health of migrants and natives in Germany - Kai Ingwersen; Stephan L. Thomsen (BMC, 2024)
Abstract Background This study explores the health status differences between migrants and native Germans, focusing on potential disparities in their workloads. Physical and mental workloads can negatively impact individual health. Since various occupations come with distinct health-related patterns, occupational selection may contribute to systematic health disparities among socio-economic groups. Given the generally poorer health of migrants, they might experience systematic workload differences overall. Methods We suggest a conceptual framework for the empirical analysis based on the theory of health as a durable good with health consumption and health investment as key parameters. We quantify the role of work tasks, job requirements and working conditions on individual health based on detailed information from the BIBB/BAuA labour force survey 2012 and 2018. Results The empirical results reveal that migrants, i.e. foreigners and German citizens with a migration background, have a higher perception of workload and related health afflictions within the same occupation. Native Germans, on the other hand, experience a higher burden by high job requirements, both physically and mentally. The findings imply heterogeneous health impacts of work for migrants and native Germans due to differences in health consumption. Conclusions The analysis shows that migrants report worse health than natives, with stronger negative effects of work-related conditions on their health, both physically and mentally. Women, in general, report poorer health conditions than men. The findings emphasize the importance of promoting human capital to reduce economic and health disparities, though caution is advised regarding affirmative actions for migrants; further research is needed to understand the underlying mechanisms and address these issues effectively.